KOMUNIKASI POLITIK: KAJIAN SUBSTANSIAL DALAM PENDEKATAN POLITIK - Thomas T. Pureklolon (Universitas Mercu Buana, 2021)
Political communication consists of political actors and political messages relating to power, governance, and all government policies. This communication takes place in complex political behavior. The complexity of political communication runs in a political process that is always unique and strategic from a communicator through messages and media. The speaking ability and representation of a communicator are the main determining elements in political communication. Political communication is a dynamic element that can determine political socialization and at the same time determine political participation. In this case political communication can be a pattern of human political behavior and a major determinant in politics. Therefore; Political communication is communication that involves political messages and political actors, or is directly related to power, government and government policies in a country. Political communication can also be understood as communication between two institutions, namely